Long term results of mechanical prostheses for treatment of active infective endocarditis. Issue 1 (1st July 2001) - Guerra, J M; Tornos, M P; Permanyer-Miralda, G; Almirante, B; Murtra, M; Soler-Soler, J
Abstract : OBJECTIVE: To analyse the long term results of mechanical prostheses for treating active infective endocarditis. DESIGN: Prospective cohort study of a consecutive series of patients diagnosed with infective endocarditis and operated on in the active phase of the infection for insertion of a mechanical prosthesis. SETTING: Tertiary referral centre in a metropolitan area. RESULTS: Between 1975 and 1997, 637 cases of infective endocarditis were diagnosed in the centre. Of these, 436 were left sided (with overall mortality of 20.3%). Surgical treatment in the active phase of the infection was needed in 141 patients (72% native, 28% prosthetic infective endocarditis). Mechanical prostheses were used in 131 patients. Operative mortality was 30.5% (40 patients). Ninety one survivors were followed up prospectively for (mean (SD)) 5.4 (4.5) years. Thirteen patients developed prosthetic valve dysfunction. Nine patients suffered reinfection: four of these (4%) were early and five were late. The median time from surgery for late reinfection was 1.4 years. During follow up, 12 patients died. Excluding operative mortality, actuarial survival was 86.6% at five years and 83.7% at 10 years; actuarial survival free from death, reoperation, and reinfection was 73.1% at five years and 59.8% at 10 years. CONCLUSIONS: In patients surviving acute infective endocarditis and receiving mechanical prostheses, the rate of early reinfection compares well with reported results of homografts. In addition, prosthesis dysfunction rate is low and long term survival is good. These data should prove useful for comparison with long term studies, when available, using other types of valve surgery in active infective endocarditis.